Differential lung ventilation via tracheostomy using two endotracheal tubes in an infant: a case report. - Demirkol, Demet; Ataman, Yasemin; Gündoğdu, Gökhan (My University, 2017)
This case report presents differential lung ventilation in an infant. The aim is to define an alternative technique for performing differential lung ventilation in children. To the best of our knowledge, this is the first report of this kind.

A 4.2-kg, 2.5-month-old Asian boy was referred to our facility with refractory hypoxemia and hypercarbia due to asymmetric lung disease with atelectasis of the left lung and hyperinflation of the right lung. He was unresponsive to conventional ventilator strategies; different ventilator settings were required. To perform differential lung ventilation, two separate single-lumen endotracheal tubes were inserted into the main bronchus of each lung by tracheotomy; the tracheal tubes were attached to discrete ventilators. The left lung was ventilated with a lung salvage strategy using high-frequency oscillatory ventilation, and the right lung was ventilated with a lung-protective strategy using pressure-regulated volume control mode. Differential lung ventilation was performed successfully with this technique without complications.

Differential lung ventilation may be a lifesaving procedure in select patients who have asymmetric lung disease. Inserting two single-lumen endotracheal tubes via tracheotomy for differential lung ventilation can be an effective and safe alternative method.
Keywords: Asymmetric lung disease; Differential lung ventilation; Infant; Single-lumen tubes; Tracheotomy